Productivity of Stored Water in Small Reservoirs for Dry Season Agriculture in the Upper East Region of Ghana - Yamoah-Antwi, Dwuodwo (2011)
A thesis submitted to the College of Engineering in partial fulfilment of the requirements of the degree of Master of Science.